1961
DOI: 10.1039/jr9610002031
|View full text |Cite
|
Sign up to set email alerts
|

386. The vapour pressure of plutonium tetrafluoride

Abstract: By C. J . MANDLEBERG and D. DAVIES.'lhe vapour pressure of plutonium tetrafluoride has been measured by Knudsen's effusion method, as modified by Phipps et al. Between 700" ant1 12OO0c, the vapour pressure can be represented by log,, p (mm. Hg) = 5-58 -10,04O/T; above 1200" a more volatile species occurs, whose vapour pressure can be represented by log,, p (mm. Hg) = 36.1 -54,18O/T.Above 1200" the residue remaining in the effusion pot is plutonium trifluoride and it is tentatively suggested that the species ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1964
1964
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The vapor pressure of plutonium tetrafluoride has been determined by two teams of investigators, both using the Knudsen effusion technique (18,65). Mandleberg and Davies (65) found that between 700 and 1200°t he vapor pressure varies with the temperature according to the equation log P (mm) = 5.58 -10,040/T Above 1200°, where a more volatile species occurs, the vapor pressure is represented by log P (mm) = 36.1 -54,180/T Above 1200°the residue is plutonium trifluoride, and they tentatively suggest that the species effusing above 1200°is the pentafluoride.…”
Section: Vapor Pressurementioning
confidence: 99%
“…The vapor pressure of plutonium tetrafluoride has been determined by two teams of investigators, both using the Knudsen effusion technique (18,65). Mandleberg and Davies (65) found that between 700 and 1200°t he vapor pressure varies with the temperature according to the equation log P (mm) = 5.58 -10,040/T Above 1200°, where a more volatile species occurs, the vapor pressure is represented by log P (mm) = 36.1 -54,180/T Above 1200°the residue is plutonium trifluoride, and they tentatively suggest that the species effusing above 1200°is the pentafluoride.…”
Section: Vapor Pressurementioning
confidence: 99%